GRAVITY ANOMALIES AND DEEP CRUSTAL STRUCTURE OF THE HOANG SA ARCHIPELAGO AREA - Huong, Nguyen Thi Thu (Vietnam Journal of Marine Science and Technology, 2007)
This paper presents some interpretation results of the gravity anomalies for investigating deep crustal structures of Hoangsa archipelago area. Based on applying the maximum horizontal gradient, 3D inversion methods and the characteristics of the gravity fields, the results show that Earth crustal structure of the study area is oriented NE-SW, included oceanic crust in the south and northeast, Maclessfield uplift. Hoangsa uplift, south Hoangsa sunk blocks and Hoangsa basin in the northwest. The Moho depth ranges from 10 to 28 km, such as, 10 - 12 km within the oceanic crust, 18 - 22 km within south Hoangsa sunk blocks, 16 - 23 within the Maclessfield uplift block, 24 - 28 km within Hoangsa uplift and 23 - 24 km within Hoangsa basin. NE-SW and NW-SE fault systems had activated strongly in the, Hoangsa uplift, Maclessfield uplift and south Hoangsa. Most NE-SW oriented faults in the south of Hoangsa uplift are dipping southeast ward. The semi meridian fault system develops mainly in the west and northeast parts of Hoangsa uplift.